The Implementation of Flipped Classroom in Teaching Descriptive Text Reading: A Case Study At Vocational High School - Kusdiana, Indah Lestari; Samsi, Yogi Setia; Kartini, Dedeh (Journal of Educational Sciences, 2025)
This study explores the implementation of the Flipped Classroom learning model in teaching descriptive text reading at Vocational High School in Karawang. In the current digital era, traditional teacher-centered learning often fails to engage students and limits their ability to develop reading comprehension skills. Flipped Classroom offers an alternative by shifting the initial learning process outside the classroom through digital materials, while face-to-face sessions are focused on discussion, problem-solving, and collaborative activities. This research employed a qualitative case study approach involving eight tenth-grade students selected through purposive sampling. Data were collected using observations, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The findings reveal that students became more active, confident, and better prepared to understand descriptive texts, while teachers benefited from more efficient class time management. Nevertheless, challenges such as limited internet access, insufficient home learning support, and time management issues were observed. The study concludes that while Flipped Classroom enhances students’ reading comprehension and classroom participation, its effectiveness depends on digital infrastructure, student discipline, and teacher facilitation. Therefore, providing training in time management, strengthening the teacher’s role as facilitator, and conducting periodic evaluations are recommended to optimize this method in vocational high schools.